A Survey on the Security of PUFs. Issue 1 (August 2021) - Su, Shuqin; Zhu, Min; Wang, Hanning; Yang, Bohan; Liu, Leibo
Abstract: Physical Unclonable Function (PUF) is an essential security block in security systems, which can be used for authentication and key generation. Its security is related to the security of the entire security system, thus it has received widespread attention and it is necessary for designers and users to know the security threats and solutions for PUFs before working on PUFs. The paper mainly introduces and summarizes a variety of side-channel attacks, machine learning attacks, and corresponding countermeasures for PUFs. Side-channel attacks are usually combined with machine learning attacks to improve the effectiveness of attacks. Attackers can use machine learning methods to achieve mathematical modeling of PUFs and most of the existing PUFs are vulnerable to machine learning attacks.